Kondisi dan Prospek Pengembangan Eksisting Ruang terbuka Hijau (RTH) Publik Kota Surakarta - Mastuti, Arum; ., Turtiantoro; Setiyono, Budi (Journal of Politic and Government Studies, 2017)
ABSTRACTThe existence of green open space continues to decrease as a result of development. Reduction in the quantity of green open space which is very significant in urban areas, causes in lower quality of urban public green open space as a consequence of the development of the city that needs a lot of land. Though the existence of public green open space is needed as one of the important elements of the urban.This research was conducted with the aim to know how the existing condition, external and internal environment aspects in the management of green open spaces by the government that affect the prospect of development of existing green open space in the future in Surakarta. The results showed that there is a big gap between the percentages of obligations (20%) with a percentage of the existing condition of public green open space that exists (9.17%). The problem of green space in the city is related with the poor distribution and maintaining of green space, ineffective implementation of the regulation, budget and land limitation for the development.The recommendation could be made to the Government of Surakarta by arranging law enforcement related to the environment, good physical planning, and standardization of for human resources recommendation in the institutions which is responsible to manages of green spaces, direct the activities of Corporate Social Responsibility (CSR) for public green open spaces. In addition, look for alternative fulfillment of public green space area with the acquisition of private land, the revitalization of green space that has undergone over the function, or through the development of green space in the special functions.Keywords: Condition, Prospect, Existing, Public Green Open Space Development